EML4-ALK-positive lung adenocarcinoma presenting an unusual metastatic pattern in a 29-year-old woman who is alive and well in her third year follow up:A case report. (2017) - Tokat, Fatma; Zeren, Handan; Barut, Pinar; Tansan, Sualp; Ince, Umit
Abstract: Non-small cell lung cancer (NSCLC) is a frequent tumor entity with high mortality. Although several newly discovered chromosomal translocations and mutations opened new horizons for targeted therapy, literature still lacks large series of NSCLC with chromosomal abberations and their correlations with histological and clinical features. We present a case of echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) translocation positive adenocarcinoma of the lung with an unusual metastatic pattern in a 29-year-old young woman. Conclusion: Young adult non-smoker female patients with an unexplained pleural effusion and signs of metastatic disease should alert the physicians straight away for all types of malignancies including lung cancer. Any skin lesions should be evaluated carefully, biopsies should be done to exclude metastasis in urgency. On the other hand, an uncommon clinical presentation of a lung cancer requires corresponding molecular testing rapidly in order to offer the best treatment option.